Retroperitoneoscopic adrenalectomy in an infant with adrenocortical virilizing tumor - Tobias-Machado, Marcos; Cartum, Jairo; Santos-Machado, Telma Murias; Gaspar, Heloísa Amaral; Simões, Alexandre Sibanto; Cruz, Ricardo; Rodrigues, Renata; Juliano, Roberto Vaz; Wroclawski, Eric Roger (São Paulo Medical Journal, 2002)
CONTEXT: Adrenocortical virilizing tumors are rare in the pediatric age group. Laparoscopic surgery is the gold standard method for treatment of adrenal functional tumors under 6 cm in size, in adults. There has been very little use of laparoscopy in children and there is no report of its application in the treatment of adrenal carcinoma in childhood. DESIGN: Case report. CASE REPORT: We performed the first laparoscopic resection using retroperitoneal access for the treatment of an adrenocortical virilizing tumor in a pediatric patient. We believe that retroperitoneoscopic access is a viable and promising option for the treatment of adrenal tumors in children.